Factors that influence student's satisfaction towards counter service at UiTM Jengka, Pahang / Abu Farhan Abdul Ghani and Mohd Azwan Ilias - Abdul Ghani, Abu Farhan; Ilias, Mohd Azwan (2013)
A study was conducted to find out the factors that influence the student's satisfaction towards counter service offered at UiTM Jengka, Pahang. It was also to examine the expectations of customers on factors that would help them to enhance their level of satisfaction towards counter service offered In order to obtain information, a questionnaire was validated by two people. Both were from the Faculty of Business Management which are the supervisor and also the lecturer. 50 of questionnaires were distributed to UiTM Jengka Pahang degree students and the return rate is hundred (100) percents. The findings showed the majority of respondents agreed that the factors of Service Quality, Service Offering, Service Facilities and Counter Staffs are importance in order to influence the student's satisfactions towards the counter service offered, most of them very satisfied with the service offered. Apart form the findings also showed that the student ranks the factors that influence their level of satisfaction and most of the respondent's rank that the service offerings in most influence to their satisfaction. Some recommendations, needed to be applied and suggested to UiTM Jengka, Pahang to increase the level of student's satisfactions. The recommendation suggested are taken form the students answers which include Service Quality, Service Offering, Service Facilities and Counter Staffs.